Fifty years of archives administration in Nigeria: lessons for the future (2007)
Purpose - In commemoration of the 50 years of archives administration in Nigeria, the purpose of this paper is to look at the establishment of the National Archives of Nigeria, its expansion and development over the years and its role in coordinating records management in Nigeria. Design/methodology/approach - The paper is based on published literature and documentary evidence from records. Findings - The paper discusses the gains of the past, particularly the high hopes of the 1970s and the expansion and consolidation of the 1980s which rolled into the early 1990s. Notes the decadence of the 1990s and highlights the problems that bedevilled the institutions and archives and records management in the country among which are poor funding, lack of appreciation of the importance of archives, obsolete equipment and high staff turn over.